Implementation of dual grid technique in BEM analysis of 3D contact problems - Aleynikov, Sergey; Sedaev, Alexander (Computer Assisted Methods in Engineering and Science, 2000)
The work is devoted to the practical application of dual grids in the boundary element method (BEM). Definitions of dual grids on the plane are given and algorithm constructing dual grid for a given triangulation is described. The problem of utilizing two numerical solutions of one problem defined on the couple of dual grids is considered and the results of this technique are demonstrated. The examples from geomechanics modelling the contact interaction of shallow foundations and elastic bases are presented.